2015
DOI: 10.19052/mv.3704
|View full text |Cite
|
Sign up to set email alerts
|

Estadio de madurez sexual en toros de la raza nelore

Abstract: La presente investigación se planteó con el objetivo de determinar el estado de madurez sexual de toros jóvenes de la raza nelore y su relación con el perímetro escrotal y las características seminales. Se estudiaron 1985 animales con edades comprendidas entre los 19 y los 23 meses de edad, alimentados con pasturas tropicales (Brachiaria brizantha, Brachiaria decumbes y Panicum maximun) y evaluados a través de examen andrológico. Se valoraron las características físicas del eyaculado, la morfología espermática… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Significant phenotypic differences have been reported for age at puberty among cattle breeds, where Zebu ( Bos indicus ) cattle breeds, such as Nelore, have slower testicular development and tend to reach puberty later than taurine ( Bos taurus ) breeds (Casas, Lunstra, Cundiff, & Ford, ; Chase et al, ; Lunstra & Cundiff, ). Ramírez López et al (), in a study to determine the stage of sexual maturity in Nelore bulls, identified that 84.5% of the bulls that were 19–23 months old were sexually mature. Freneau, Vale Filho, Marques, and Maria () identified that some young Nelore bulls were mature when they were around 15 months old.…”
Section: Introductionmentioning
confidence: 99%
“…Significant phenotypic differences have been reported for age at puberty among cattle breeds, where Zebu ( Bos indicus ) cattle breeds, such as Nelore, have slower testicular development and tend to reach puberty later than taurine ( Bos taurus ) breeds (Casas, Lunstra, Cundiff, & Ford, ; Chase et al, ; Lunstra & Cundiff, ). Ramírez López et al (), in a study to determine the stage of sexual maturity in Nelore bulls, identified that 84.5% of the bulls that were 19–23 months old were sexually mature. Freneau, Vale Filho, Marques, and Maria () identified that some young Nelore bulls were mature when they were around 15 months old.…”
Section: Introductionmentioning
confidence: 99%